2015
DOI: 10.1016/j.wocn.2015.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Listeners use intonational phrase boundaries to project turn ends in spoken interaction

Abstract: In conversation, turn transitions between speakers often occur smoothly, usually within a time window of a few hundred milliseconds. It has been argued, on the basis of a button-press experiment [De Ruiter, J. P., Mitterer, H., & Enfield, N. J. (2006). Projecting the end of a speaker's turn: A cognitive cornerstone of conversation. Language, 82(3):515–535], that participants in conversation rely mainly on lexico-syntactic information when timing and producing their turns, and that they do not need to make use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
124
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 38 publications
6
124
0
2
Order By: Relevance
“…Overall, participants made few anticipatory switches after non-questions, even in the English videos when they had full linguistic access. Prior work using online, metalinguistic tasks has shown that participants can use linguistic cues to accurately predict upcoming turn ends (Bögels & Torreira, 2015;Magyari & De Ruiter, 2012;De Ruiter et al, 2006). The current results add a new dimension to our understanding of how listeners make predictions about turn ends: both children and adults spontaneously monitor the linguistic structure of unfolding turns for cues to imminent responses.…”
Section: Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…Overall, participants made few anticipatory switches after non-questions, even in the English videos when they had full linguistic access. Prior work using online, metalinguistic tasks has shown that participants can use linguistic cues to accurately predict upcoming turn ends (Bögels & Torreira, 2015;Magyari & De Ruiter, 2012;De Ruiter et al, 2006). The current results add a new dimension to our understanding of how listeners make predictions about turn ends: both children and adults spontaneously monitor the linguistic structure of unfolding turns for cues to imminent responses.…”
Section: Discussionmentioning
confidence: 63%
“…Prior work with adults has found a consistent role for lexicosyntax in predicting upcoming turn structure (De Ruiter et al, 2006;Magyari & De Ruiter, 2012), whereas the role of prosody is still under debate (Duncan, 1972;Ford & Thompson, 1996;Bögels & Torreira, 2015). Knowing that children comprehend more about prosody than lexicosyntax early on (see Speer & Ito (2009) for a review), we thought it possible that young children would instead show an advantage for prosody in their predictions about turn structure in conversation.…”
Section: Predicting Upcoming Turn Structurementioning
confidence: 96%
See 3 more Smart Citations